A novel OXA-10–like β-lactamase is present in different Enterobacteriaceae - Porto, Ayelen Patricia (2010)
OXA 101, a novel OXA-10 like enzyme, was found forming part of a class 1 integron located in a conjugative plasmid in three different species of Enterobacteriaceae. This β-lactamase is related to OXA-35 and OXA-56 and displays a narrow substrate hydrolysis profile.